Histological Differentiated/Undifferentiated Mixed Type Should Not Be Considered as a Non-Curative Factor of Endoscopic Resection for Patients With Early Gastric Cancer - Tang, Xiaolong; Zhang, Mengjun; He, Qingsi; Sun, Guorui; Wang, Chao; Gao, Peng; Qu, Hui (Frontiers in Oncology, 2020)
Background Histological differentiated/undifferentiated mixed-type adenocarcinomas are frequently found in patients with early gastric cancer (EGC). Yet it is unclear whether these mixed-type adenocarcinomas can be treated by endoscopic resection (ER) in EGC patients. Aims To evaluate the lymph node metastasis (LNM) rate and long-term outcomes in mixed-type EGC patients and assess the feasibility of ER in these patients. Methods Clinicopathological features, risk factors of LNM, and overall survival (OS) and progression-free survival (PFS) rates of EGC patients were analyzed according to different histological types. Results Patients with mixed-type EGC had higher LNM rates than patients with non-mixed-type EGC (11.4 vs. 6.2%, P = 0.044). In the multivariate analysis, larger tumor diameter, presence of an ulcer, submucosal invasion, histological undifferentiated type, histological mixed type, and lymphovascular invasion resulted as independent risk factors for LNM in EGC patients (all P < 0.05). The LNM rate in mixed-type patients who met the Japanese ER criteria was 3.3%, including fulfilling the absolute criteria 0%. The 5-year OS and PFS rates in mixed-type patients were 94.59 and 91.47%, respectively. There was no statistical significance in the OS (P = 0.870) and PFS (P = 0.705) between mixed-type and non-mixed-type EGC patients fulfilling the Japanese ER criteria. Conclusion Histological differentiated/undifferentiated mixed type in EGC patients meeting the Japanese absolute criteria for ER are associated with low risk of LNM and favorable prognosis, and thus, it should not be considered as a non-curative factor for ER.